Comparative study of mechanical properties of direct core build-up materials - Girish Kumar; Amit Shivrayan (Wolters Kluwer Medknow Publications, 2015)
Background and Objectives: The strength greatly influences the selection of core material because core must withstand forces due to mastication and para-function for many years. This study was conducted to evaluate certain mechanical properties of commonly used materials for direct core build-up, including visible light cured composite, polyacid modified composite, resin modified glass ionomer, high copper amalgam, and silver cermet cement. Materials and Methods: All the materials were manipulated according to the manufacturer's recommendations and standard test specimens were prepared. A universal testing machine at different cross-head speed was used to determine all the four mechanical properties. Mean compressive strength, diametral tensile strength, flexural strength, and elastic modulus with standard deviations were calculated. Multiple comparisons of the materials were also done. Results: Considerable differences in compressive strength, diametral tensile strength, and flexural strength were observed. Visible light cured composite showed relatively high compressive strength, diametral tensile strength, and flexural strength compared with the other tested materials. Amalgam showed the highest value for elastic modulus. Silver cermet showed less value for all the properties except for elastic modulus. Conclusions: Strength is one of the most important criteria for selection of a core material. Stronger materials better resist deformation and fracture provide more equitable stress distribution, greater stability, and greater probability of clinical success.